Farmers perceptions and adoption of new agricultural technology: evidence from analysis in Burkina Faso and Guinea, West Africa - Adesina, A.; Baidu-Forson, Joseph Jojo (Wiley, 1995)
Economists investigating consumer demand have accumulated considerable evidence showing that consumers generally have subjective preferences for characteristics of products and that their demand for products re-significantly affected by their perceptions of the product's attributes. However, the role of farmers, preferences on adoption decisions have received very limited attention in adoption studies conducted by economists. This paper tests the hypothesis that farmers' perceptions of technology characteristics significantly affect their adoption decisions. The analysis, conducted with Tobit models of modern sorghum and rice varietal technologies in Burkina Faso and Guinea, respectively, strongly supports this hypothesis. Our results provide a strong case for future adoption studies to expand the range of variables used away from the broad socio-economic, demographic and institutional factors to include farmers' subjective perceptions of the characteristics of new agricultural technologies.